2019
DOI: 10.21203/rs.2.17685/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The incidence of depression and anxiety in patients with ankylosing spondylitis: A systematic review and meta-analysis

Abstract: Background: As awareness for the importance of mental health continues to expand in rheumatology, it is important to understand the epidemiology of psychiatric complications in ankylosing spondylitis (AS) with the ultimate goal of future prevention and improved quality of care. This study aims to review evidence on the incidence and determinants of depression and/or anxiety among patients with AS. Methods: We searched Medline, Embase, Cochrane Database of Systematic Reviews, CINAHL Complete, and PsycINFO for f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Methodological quality and risk of bias were assessed using the Newcastle Ottawa Scale for Observational Studies (28), which was modified to meet the requirement of this study (29). A total of six criteria were evaluated: representativeness of the population, sample size, statistical analysis, missing data, methodology to report the outcome of interest and methods to detect or report the outcome of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Methodological quality and risk of bias were assessed using the Newcastle Ottawa Scale for Observational Studies (28), which was modified to meet the requirement of this study (29). A total of six criteria were evaluated: representativeness of the population, sample size, statistical analysis, missing data, methodology to report the outcome of interest and methods to detect or report the outcome of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Three systematic literature reviews and meta-analyses on the prevalence of depression in AS and PsA are reported. 31,37,38 The largest meta-analysis included 19,263 patients with AS from 33 studies conducted in Europe, Asia and South America. These studies measured depression using a variety of methods including self-report, validated questionnaires, clinical interviews, administrative and hospital records.…”
Section: Prevalence and Incidence Of Depression In Patients With As Omentioning
confidence: 99%
“…In one meta-analysis, the pooled prevalence of depression in AS was reported to be 29%. 37 However, findings from this meta-analysis were largely driven by one large study from Taiwan comprising 11,701 patients, 39 which used the Elixhauser comorbidity index to record ICD-9 identified diagnoses of depression, 40 rather than direct assessment of mood using a validated scale/interview. Reliance on clinical diagnosis can lack temporal validity, provides no information on current symptom severity, and may underestimate prevalence due to subthreshold and undiagnosed depression.…”
Section: Prevalence and Incidence Of Depression In Patients With As Omentioning
confidence: 99%
See 2 more Smart Citations